Improving Management of Type 2 Diabetes Mellitus in Hospitalized Adults: A Quality Initiative. Issue 2 (3rd March 2021) - Wahlberg, Elizabeth A.; Muthukrishnan, Preetika; Burnett, Maria; Barrett, Kaitlyn V.; Gilbert, Matthew; Repp, Allen B.
Abstract : Supplemental Digital Content is Available in the Text. ABSTRACT: The American Diabetes Association recommends scheduled basal and nutritional insulin doses as the preferred treatment for noncritically ill hospitalized patients with type 2 diabetes; however, the adoption of these practices remains suboptimal. We sought to understand current diabetes management practices and improve glycemic control in patients with type 2 diabetes on the Hospital Medicine Services at our academic medical center. We surveyed resident and attending physicians to understand barriers to guideline-based practice. We conducted educational sessions, developed pocket-card decision aids, encouraged discussion on rounds, and provided periodic performance feedback to attending physicians. Results of the barriers survey identified "fear of causing hypoglycemia" as the most common barrier to guideline-based practice. Compared with the preintervention 12-month period, these interventions were associated with doubling of the use of guideline-based insulin therapy regimens, a significant reduction in the rate of severe hyperglycemia days, and a nonsignificant reduction in the rate of hypoglycemia days over a 12-month period. These results demonstrate that a simple, low-cost intervention can be associated with an increase in guideline-concordant insulin ordering with improvement in glycemic outcomes for patients with type 2 diabetes.